Shakespeare checks into the digital world: rewriting his plays using Emojis - Marcia Amaral Peixoto Martins; Ofélia da Conceição Machado Sagres (Cadernos de Tradução)
This study analyzes the OMG Shakespeare series, which aims at bringing Shakespeare’s plays to young audiences using digital language. The series features rewritings of Shakespeare’s plays into WhatsApp-message format. There are four titles available: srsly Hamlet, Macbeth #killingit, YOLO Juliet and A Midsummer Night #nofilter. The analysis seeks to determine: i) the general concept of the series; ii) the main strategies used in the intermedial adaptation of the plays and iii) the relationships between verbal and visual languages in the texts. The theoretical framework relies on Irina Rajewisky’s (2010) and Werner Wolf’s (1999) concepts of intermediality, Charles Peirce’s (1998) theory of signs, Lars Elleström’s (2010, 2013) conceptual framework on modality and media and on Linda Hutcheon’s (2013) concepts of adaptation.